Halal Awareness and Halal Literacy Index of Community: A Determinants Study in the Sociocultural Context of Penginyongan - Muarrifah, Safrina; Ida Puspitarini W (Mabsya: Jurnal Manajemen Bisnis Syariah, 2023)
This study aims to determine the partial and simultaneous effect of religiosity, awareness of healthy lifestyles, halal certificate logos, exposure media and halal literacy on the level of halal awareness of halal food products in the sociocultural group of the Penginyongan community. The study used 200 respondents with a non-probability method through purposive sampling. Where the respondents in this study have a special characteristic, namely using Penginyongan language actively in their daily lives. Data through questionnaires in this study were processed using multiple linear regression analysis. The results showed that religiosity, media exposure and halal literacy had no partial effect on the level of halal awareness of halal food products in the sociocultural group of the Penginyongan community. There are only 2 variables that have a significant partial effect, namely a healthy lifestyle and the halal certificate logo. Simultaneous testing resulted in the conclusion that all independent variables simultaneously had a significant effect on the dependent variable, that is halal awareness. In the sociocultural group of Penginyongan community was also found to still use a social perspective/perception about the halalness of a product, not looking at the special characteristics of halal listed on the label/packaging of food products.